A novel translocation t(11;13) (q21;q14.2) in a child with suprasellar primitive neuroectodermal tumor and retinoblastoma. (June 2013) - Huddleston, Stephen; McNall-Knapp, Rene Y.; Siatkowski, Michael; Odom, Christine; Brennan, Rachel; Wilson, Matthew W.
<x xml:space="preserve">Abstract</x> Purpose: To report on a novel translocation related to a suprasellar primitive neuroectodermal tumor (sPNET) and retinoblastoma. Design: Case report. Methods: A 6-year-old girl underwent genetic testing after developing unilateral retinoblastoma subsequent to treatment (surgery, chemotherapy, and stem-cell rescue) for a sPNET found at 1 year of age. Results: Genetic testing found the girl's karyotype to be 46, XX, t(11;13)(q21;q14.2); a novel translocation not previously reported in patients with either retinoblastoma or sPNET. Conclusions: Our patient had a novel translocation affecting the retinoblastoma 1 (RB1) gene, 46, XX, t(11;13)(q21;q14.2) resulting in the late development of unilateral retinoblastoma. Although she only developed unilateral retinoblastoma, her central nervous system was affected at a very early age. How her complex mutation resulted in retinoblastoma and antecedent sPNET remains unknown.